Meningkatkan Kinerja Karyawan Melalui Green Human Resource Management: Peran Mediasi Green OCB Dan Green Behavior - Riyanto, Fery; Mujib, Miftachul; Damar, Haunan (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This study explores how Green HRM and Green OCB mediate organizational performance at Blue Pearl Company in Singapore Methods: This study uses quantitative methods. Data analysis uses Partial Least Square (PLS) with Smart-PLS3 software. Finding: The study confirmed that Green Human Resource Management (GHRM) significantly influences green behavior and organizational citizenship behaviors (OCB) related to sustainability, which in turn positively impacts employee performance. Specifically, GHRM indirectly enhances performance through both green behavior and green OCB. However, it was found that GHRM does not directly lead to an improvement in employee performance Theoretical contribution/Originality: These results contribute theoretically by providing empirical evidence of the influence of GHRM on improving employee performance through mediation played by green behavior and green OCB Practitioner implication: This research contributes as encouragement for companies operating in the manufacturing sector to implement GHRM as a way to improve individual employee performance Research limitation: The review of sustainability values in the future needs to be reviewed because concern for environmental sustainability in green parks will provide benefits for companies in increasing their sustainability values